The Influence Of Communication And Organizational Climate On The Participation Of Parents In The Provision Of Education Kinderfield Elementary School In Indonesia - Sri Ovaningsih; Nurhattati Fuad; Siti Zulaikha (Journal Research of Social Science, Economics, and Management, 2024)
This research explores the impact of communication and organizational climate on parental engagement within Kinderfield Elementary School's educational provision in Indonesia. The study aims to investigate how effective communication between school stakeholders and a positive organizational environment influence parents' active participation in their children's education. By examining this relationship, we seek to provide valuable insights for enhancing collaborative efforts among all parties involved in fostering student success. Our findings will contribute to the existing body of knowledge regarding factors that promote meaningful involvement from parents in Indonesian schools.